New Zealand 2026 - Mills, Rachel (Eyewitness travel guides., 2025)
Welcome to New Zealand, the land of the long white cloud. Whether you're seeking your next adrenaline-fix, the best places to learn more about Maori culture, or the perfect geothermal pool to unwind in, your 'DK Eyewitness' travel guide makes sure you experience all that New Zealand has to offer. An explosion of dramatic scenery, this far-flung Pacific island has it all: mammoth mountains, icy-blue glacial lakes, unspoiled coastlines, idyllic vineyards and cool, cultural cities.